Pre-weld Varestraint 시험을 이용한 CM247LC 초내열합금 보수용접부 액화균열 민감도 평가 - 정예선; Ye-seon Jeong; 정진곤; Jingon Jeong; 김세윤; Se-yun Kim; 배성환; Sung-hwan Bae; 이의종; Uijong Lee; 이형수; Hyungsoo Lee; et al. (대한금속·재료학회지, 60(4), 2022)
In this study, the liquation cracking susceptibility in the heat-affected zone of CM247LC superalloy gas turbine blades during repair welding was quantitatively evaluated using a newly developed pre-weld Varestraint test method. The repair welding geometry was replicated through Varestraint tests for the preweld bead. The liquation cracking susceptibility, that is, the liquation cracking temperature range (LCTR), could be evaluated through temperature visualization at the time of crack formation during the Varestraint test. The LCTR of CM247LC alloy repair welds (heat-affected zone of the second layer weld) was 280 K. Compared to the LCTR of as-cast (620 K) and aged (65 K) CM247LC, metallurgical mechanisms for controlling the LCTR of repair welds were examined based on the microstructural characterization and Scheil’s solidification calculations for the pre-weld. The LCTR of the CM247LC alloy repair weld was influenced by the MC carbide fraction and the segregated concentration of trace and impurity elements, such as B and S in pre-weld solidification path. A process design capable of reducing the fraction of MC carbides and solidification segregation of trace impurity elements is required. Based on the experimental and theoretical results, the proposed modified Varestraint testing method for dissimilar welds is expected to analyze the solidification cracking behavior effectively in manufacturing high-soundness CM247LC superalloy welds. (Received September 28 2021; Accepted November 8, 2021)